OPTIMALISASI PENGETAHUAN AKUNTANSI MELALUI PRAKTIKUM SOFTWARE AKUNTANSI - Anggadini, Sri Dewi; Surtikanti, Surtikanti; Junniyawati, Erika; Suryadi, Yerdaniati Putri; Damayanti, Sari (Jurnal Riset Akuntansi, 2025)
The Accounting software commonly used includes MYOB and Accurate, both of which are integrated bookkeeping software with a large number of users. Their main advantages are ease of use and the ability to automatically generate financial reports, making them superior compared to other accounting software. With their ability to process data automatically, quickly, and accurately, these tools provide significant benefits in company management. Additionally, this software is highly suitable for the needs of small and medium-sized enterprises in Indonesia. This study employs a descriptive quantitative research method, utilizing questionnaires as the primary analytical tool for each variable indicator. The respondents of this research are accounting students at Universitas Komputer Indonesia (UNIKOM) who are currently enrolled in or have completed the Accounting Software Practicum course in the odd semester (semesters 2, 4, and 6). The sampling technique used is purposive sampling, with a total of 70 respondents. The results of the study indicate that mastering and utilizing accounting technology requires students to develop a comprehensive understanding and proficiency in using this technology.